2020
DOI: 10.1186/s40729-019-0204-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation among laser-treated, machined, and sandblasted/acid-etched implant surfaces: an in vivo histologic analysis on sheep

Abstract: The aim of the present in vivo analysis was to evaluate the osseointegration process of titanium implants with three different surfaces (machined, sandblasted and acid-etched, and laser-treated) after 15 and 30 days of healing period. Materials and methods: Thirty-six implants with different surfaces were placed in the iliac crest of four Bergamasca sheep. The implant surfaces tested were sandblasted and acid-etched (group A), laser-treated (group B), and fully machined (group C). Two animals were sacrificed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
(25 reference statements)
2
20
0
Order By: Relevance
“…Anodizing treatment increased hydrophilicity of pure Ti and Ti2448 alloy as well as promoted ECM mineralization in human BMDSCs. In another study, De Tullio et al [125] demonstrated using a sheep model that SLA-or laser-treated Ti substrates supported osseointegration in vivo. In turn, Kunrath et al [130] applied acid etching and anodizing methods to alter physicochemical properties of Ti substrate in order to improve biocompatibility of the material.…”
Section: Subtractive Modifications Of Biomaterials Surfacementioning
confidence: 97%
See 1 more Smart Citation
“…Anodizing treatment increased hydrophilicity of pure Ti and Ti2448 alloy as well as promoted ECM mineralization in human BMDSCs. In another study, De Tullio et al [125] demonstrated using a sheep model that SLA-or laser-treated Ti substrates supported osseointegration in vivo. In turn, Kunrath et al [130] applied acid etching and anodizing methods to alter physicochemical properties of Ti substrate in order to improve biocompatibility of the material.…”
Section: Subtractive Modifications Of Biomaterials Surfacementioning
confidence: 97%
“…Laser treatment of the implants is an innovative surface modification method which allows modification of the surfaces at a nano-, micro-, and macro-size scale using a stationary laser beam. Major advantages of the laser treatment include possibility to modify both chemistry and surface topography and no necessity to use any acid and metal sand which significantly reduces risk of contamination of the modified surface compared to other techniques [125,126].…”
Section: Subtractive Modifications Of Biomaterials Surfacementioning
confidence: 99%
“…Trisi et al [47] demonstrated, in an in vivo animal study, that laser-treated implants had significant higher bone to implant contact percentages (%BIC) and reverse torque values in respect to machined implants. Other authors [48] found no significant differences in %BIC values comparing laser-treated and sandblasted/acidetched implants in sheep.…”
Section: Discussionmentioning
confidence: 84%
“…Although the laser treated surface implant was cleaner and more uniform than the acid etched surface implant, there were no significant differences found between both. Also, De Tulle et al study in 2020 (30) made a comparative evaluation among laser treated, machined, and acid etched implant surfaces on sheep and observed good osseointegration in both acid etched and laser surface implant with no significant differences in the bone to implant contact percentage comparing acid-etched and laser-treated surface implants.…”
Section: Discussionmentioning
confidence: 99%